Study about Piano Education in Contemporary China - Liu, Lingran (An Overview of Literature, Language and Education Research Vol. 3, 2024)
At the beginning of the 19th century, the elegant piano was introduced into China and became a well-known Western instrument. Parents in the education of their children, also pay more attention to piano education, which sets off a wave of learning piano upsurge. This paper analyzed the reasons why piano education can present such a strong popularity through personal practice and preliminary exploration of the current piano education. Piano learning is of great benefit to the growth of children and the development of people. The paper also made a series of reflections on some problems existing in the current piano education, including the talent and enjoyment of piano children, blind parents, training institutions and teachers, Immature grading and competition system. Then we reflected on the current situation of contemporary Chinese piano education. The future Chinese piano education should pay attention to the above problems and create a better music learning environment.